Screening for Sulfur Compounds by Molybdenum-Catalyzed Oxidation Combined with Liquid Chromatography-Mass Spectrometry - Hirotaka Matsuo; Yu Hanamure; Rei Miyano; Yōko Takahashi; Satoshi Ōmura; Takuji Nakashima (Molecules, 2020)
The molybdenum (Mo)-catalyzed oxidation of sulfide under neutral conditions yields sulfone. This reaction proceeds more smoothly than olefin epoxidation and primary or secondary alcohol oxidation. In this study, Mo-catalyzed oxidation was used to screen for sulfur compounds (named “MoS-screening”) in microbial broths by liquid chromatography-mass spectrometry (LC/MS). To demonstrate proof-of-concept, known sulfur microbial compounds were successfully identified from a mixture of non-sulfur microbial compounds as sulfinyl or sulfonyl products of Mo-catalyzed oxidation. Then our MoS-screening method was used to screen 300 samples of microbial broth for sulfur compounds. One of the identified compounds was a kitasetaline-containing N-acetyl cysteine moiety produced by an actinomycete strain. These results demonstrate the potential of MoS-screening in the search for new sulfur compounds from microbial sources.